Women, politics and the media : the 1999 New Zealand general election : a thesis presented in partial fulfilment of the requirements for the degree of PhD in Communication & Journalism at Massey University, Palmerston North, New Zealand - Fountaine, Susan Lyndsey (Massey University, 2002)
New Zealand's shift to a Mixed Member Proportional (MMP) system of government contained a two-fold promise for women. Explicitly, there was the prospect of increased electoral diversity, meaning more women in Parliament, and implicitly, there was a promise of better political reporting and therefore qualitatively better coverage of women. The country's second proportional representation election campaign, in 1999, appeared to deliver on these promises. The 1999 General Election was historically significant because it featured two women - incumbent Jenny Shipley and Labour leader Helen Clark - contesting the role of Prime Minister. Female politicians also featured in important electorate races, and made the headlines during New Zealand First's gender-based list controversy. According to one media commentator, women determined the outcome, dominated the news and changed the nature of the campaign (Harris, 2000). However, popular opinion that women influenced the character of the campaign, and especially that they dominated the campaign, is in contrast to empirical research, from around the world, which has consistently suggested women politicians receive less news coverage, are "framed" or packaged in stereotypically feminine ways, and ultimately disadvantaged by traditional news coverage (e.g. Bathla, 1998; Braden, 1996; Gidengil & Everitt, 1999; Herzog, 1998; Norris, 1997c; van Acker, 1999). Therefore, the main aim of this study was to explore, using a combination of corroborative methodologies, how and why the news media covered female politicians during the 1999 election campaign. Three methodologies (content analysis, qualitative interviews, and a case study), and a framing typology, were employed. Content and frame analysis showed that female politicians were used as news subjects to a comparable, if not better, extent than men but were marginalised as political news sources. In other words, there was a tendency for women to be talked about, rather than talked to. This reflects dominant news structures and, in some cases, the women's own approach to self-promotion. It was also revealed that female politicians were subjected to more polarised media coverage, influenced by status, incumbency and context, and again, partly a result of their own positioning. There were significant differences in media coverage of men and women, but framing of political news did little to advance women's perspectives, suggesting election campaigns that ostensibly feature women are not necessarily of a different nature. Overall, these results suggest a blurring of the traditional "public/private" dichotomy, as an outcome of changes in the media (such as the contemporary trends toward personalisation and "celebrification") and women's campaigning. Gender remains a factor in the presentation and interpretation of political women, by the news media (which, for example, portrayed the female leaders as Xena princesses) and by the women themselves (for example, Shipley portrayed herself as a mother figure). To some extent, there appears to have been a maturing of political journalism about women but it is too soon to tell if the shift to MMP has resulted in any significant longterm change for female politicians. However, this unique study, in examining the media-politics-gender nexus in the 1999 General Election campaign, focuses attention on the two-fold promise of MMP for women, and explores the extent to which the new political system and the media have begun to deliver. On a practical level, the thesis concludes that it is important to encourage female politicians to work within, and use the current system to their advantage. However, it also urges researchers to take a critical approach to exploring the systemic socialisation and pervasive news structures, processes and values that contribute to women's ongoing political marginalisation. Finally, the thesis considers the wider implications for women, the news media, and the electoral system.
Keywords: New Zealand general election 1999; New Zealand Parliament; Women politicians; Women in mass media; Public opinion; New Zealand